Water and Wastewater Services in the Danube Region : Slovakia Country Note - World Bank (Washington, DC, 2015)
In order to evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment was done, taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess sector sustainability is included in the Annex of the State of the Sector Regional Report from the Danube Water Program. The outcomes of this assessment for the Slovak Republic water sector are displayed, which also shows average and best practices in the Danube region. The country sector sustainability score is 82, which is far above the Danube average sustainability score of 64, and among the best practices in the region. The assessment shows that, on average, the country performs well in terms of continuity of service, access to piped water and flush toilets, wastewater compliance, staffing level, nonrevenue water, and collection ratio. The main deficiencies of the Slovak water sector identified through the sector sustainability assessment are the level of investment, the operating cost ratio and the wastewater treatment coverage.